Resistance of maize to fall armyworm (Spodoptera frugiperda) in Africa - (:unkn) unknown (My University, 2023)
The fall armyworm (FAW), Spodoptera frugiperda (Lepidoptera: Noctuidae), a maize pest native to the Americas, was first reported in West and Central Africa in 2016, before invading nearly all sub-Saharan Africa (SSA) in 2017. This new pest causes an estimated 9.4 billion dollars in annual maize yield losses of maize and severely threatens food security in SSA. Faced with this threat, several means of control have been launched by several national and international agricultural research institutions. In the context of the search for rapid solutions, other than the use of synthetic pesticides, the first work undertaken consisted in using silica, a known inducer of plant resistance to biotic and abiotic stresses. A greenhouse study showed that an increase in the silica content of the plant disturbed the development of the larvae of one of the two African populations of FAW. In parallel, a strategy to control FAW in Africa by using host plant resistance from tropical maize germplasm was developed. In this context, an intensive screening against FAW was conducted by artificial infestation in the greenhouse in Kenya between 2017 and 2018 on about 3000 maize lines available in the germplasm collection of the International Maize and Wheat Improvement Center (CIMMYT). Among these lines, four (CKSBL10008, CML71, CML125, and CML370) were found to be resistant to FAW. However, information on the heredity, mechanisms and chemical basis of resistance of these lines was not known. This thesis showed that: 1) for heredity of resistance, heterosis values indicated an increase in resistance of hybrids over the average of inbred line parents. General (GCA) and specific (SCA) combining ability as well as reciprocal were a highly significant source of variation for the inheritance of resistance. CML71 and CKSBL10008 proved to be the best general combiners based on GCA effects for leaf feeding damage. Non-additive genetic effects were highly source of variation for the inhe
Keywords: African Research